Acknowledgement to Editors and Scientific Referees 2021 - Matheus Fernando Manzolli Ballestero; Alexandre Canheu; Alexandre Varella Giannetti; Artur Henrique Galvão Bruno da Cunha; Aline Saré; Amanda Lopez; Angelo Silva Neto; Carlos Eduardo Barros Jucá; Daniel Dante Cardeal; Guilherme Podolsky-Gondim; Gustavo Sampaio; Jaqueline Garcia de Almeida Ballestero; et al. (Brazilian Society for Pediatric Neurosurgery, 2022)
A scientific  journal's  greatest responsibility  is  to ensure  that  all  contributions  accepted for publications are rigorously but fairly reviewed. The Editor-in-Chief and Archives of Pediatric Neurosurgery gratefully acknowledge the qualified and regular collaboration of renowned medical doctors and scientists who kindly devoted their time to constructively review  the  submitted  articles.  Their  expertise  and  invaluable  assistance  contributed  to maintain a high scientific standard for APN. We are thus indebted to the Editorial Board members and  the  following  experts  who  reviewed  papers  and  completed  the  peer-reviewing process within 2021.